Is Architectural Drawing a Language? Symbols, Signs, Pictograms, Ideograms and Drawings - Angel Allepuz; Carlos L. Marcos (Diségno)
Articulate language was established in the 20th century as the superior model of thought. It claimed a monopoly on the model of rational thought, even advocating a homomorphism between language and brain structure. We defend here the autonomy of architectural drawing over any linguistic discipline with the arguments that will be developed in six fields of debate. This analysis will argue why, stricto sensu, architectural drawing should not be considered a language. In our view, drawings do not ‘mean’ anything; rather, they either represent or shape the world. The lack of correlation between a syntactic and semantic field denies one of the basic principles of language. Drawing, especially architectural drawing, is based on the mathematical analysis process of Euclid’s geometry and does not require deductive reasoning based on logical or natural language. Neither does conceptual art based on language models seem to have produced remarkable works of art, nor has the attack on the visual brought even some of what was promised. Goodman’s symbol system models have provided a more useful way to understand the specifics of architectural drawing as part of a representational symbolic system, beyond ‘languages and notations’. Finally, neuroscience posits the coexistence, without privilege, of a visual cognitive style as distinct from verbal cognitive style.